2022
DOI: 10.1088/1361-6579/ac7695
|View full text |Cite
|
Sign up to set email alerts
|

A novel multi-scale 2D CNN with weighted focal loss for arrhythmias detection on varying-dimensional ECGs

Abstract: Objective. The ECG is a standard diagnostic tool for identifying many arrhythmias. Accurate diagnosis and early intervention for arrhythmias are of great significance to the prevention and treatment of cardiovascular disease. Our objective is to develop an algorithm that can automatically identify 30 arrhythmias by using varying-dimensional ECG signals. Approach. In this paper, we firstly proposed a novel multi-scale 2D CNN that can effectively capture pathological information from small-scale to large-scale f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“… [105] (2021) ResNet PhysioNet-2021 A ResNet deep neural network architecture with a multi-head attention mechanism foe accurate ECG classification. [106] (2022) 2D-CNN PhysioNet-2021 A multi-scale deep neural network with weighted focal loss for ECG arrhythmias classification on varying dimensional inputs. [107] (2021) Boosting PhysioNet-2021 A mel-frequency cepstrum and amplitude-time heart variability features, handcrafted for ECG arrhythmia classification.…”
Section: Efficient Models For Ecg Cardiac Rhythm Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“… [105] (2021) ResNet PhysioNet-2021 A ResNet deep neural network architecture with a multi-head attention mechanism foe accurate ECG classification. [106] (2022) 2D-CNN PhysioNet-2021 A multi-scale deep neural network with weighted focal loss for ECG arrhythmias classification on varying dimensional inputs. [107] (2021) Boosting PhysioNet-2021 A mel-frequency cepstrum and amplitude-time heart variability features, handcrafted for ECG arrhythmia classification.…”
Section: Efficient Models For Ecg Cardiac Rhythm Classificationmentioning
confidence: 99%
“…Xia et al [106] recently proposed a novel multi-scale 2D CNN that can accurately identify 30 arrhythmias from 12-lead, 6-lead, 4-lead, 3-lead, and 2-lead ECG signals. Furthermore, they demonstrated that reduced-lead models could achieve comparable classification performance to the standard 12-lead model.…”
Section: Efficient Models For Ecg Cardiac Rhythm Classificationmentioning
confidence: 99%